Conversational Implicature Of Women’s Language By Shin Tanokura In Drama Series Of Oshin - Eko Kurniawan; Shofi Mahmudah Budi Utami (Universitas Diponegoro, 2021)
This study aims to describe the conversational implicature of women’s language by Shin Tanokura in the drama series of Oshin. Research-based on a theory of Azuma (2009) for implicature as women’s language and Yule (2006) for conversational implicature. It is a kind of qualitative research. The data collection technique used is the observing method. The method used in this research is the descriptive analysis with Connect and Compare Equation Technique and Connect and Distinguishing Technique. The result showed that the conversational implicature of women’s language by Shin Tanokura in the drama series of Oshin is generalized conversational implicature, particularized conversational implicature, and scalar implicature. These three implicatures present markers that confirm the utterances belong to the variety of women’s language. In conclusion, the use of the implicature with high intensity is a marker of the utterance that belongs to the variety of women’s language. The variety of women’s language with the use of implicature gives an impression and an image about the characteristic of women and the variety of women’s language.